Compassion Fade: Affect and Charity Are Greatest for a Single Child in Need - Västfjäll, Daniel; Slovic, Paul; Mayorga, Marcus; Peters, Ellen (PLOS ONE, 2014)
Charitable giving in 2013 exceeded 300 billion, but why do we respond to some life-saving causes while ignoring others? In our first two studies, we demonstrated that valuation of lives is associated with affective feelings (self-reported and psychophysiological) and that a decline in compassion may begin with the second endangered life. In Study 3, this fading of compassion was reversed by describing multiple lives in a more unitary fashion. Study 4 extended our findings to loss-frame scenarios. Our capacity to feel sympathy for people in need appears limited, and this form of compassion fatigue can lead to apathy and inaction, consistent with what is seen repeatedly in response to many large-scale human and environmental catastrophes.